Pengaruh Berbagai Macam Media terhadap Pertumbuhan Bibit Kelor (Moringa oleifera Lam.) Asal Stek Batang - Sawaludin Sawaludin; Aluh Nikmatullah; Bambang Budi Santoso (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2018)
This study aimedseedling derived from stem cutting to determine the effect of various media on the growth of drum stick (Moringa oleifera Lam.). Experiment was conducted from March to May 2017 in the nursery located in Dasan Agung, Mataram, with altitude of 16 meters above sea level. The method was experimental method with 6 media treatments: soil, soil+sawdust, soil+cocopeat, soil+corncob, soil+bamboo leaf, and soil+charcoal rice husk. The experimental design was Completely Randomized Design with 5 replications and 5 unit series. The result shows that the media significantly effect on the growth ofsedling stem cutting. The best media forseedling derived from stem cutting were mixture media of soil+ricecharcoal andsoil+cocopeat